Spatial distribution of adult Dectes texanus (Leconte, Coleoptera: Cerambycidae) and its effects on Kansas soybean (Glycine max L.) - Harris, Alice (Kansas State University, 2019)
Dectes texanus LeConte (Coleoptera: Cerambycidae), Dectes stem borer, is native to North American and can be found throughout Kansas in areas with soybean (Glycine max, L) production fields. In Kansas, adult D. texanus are present in production soybean fields between mid-June and September most years; however, the larval stage is the most damaging stage to the plant, due to pith removal and consequent girdling of the main stem prior to overwintering. Although loss from physiological (i.e., indirect feeding of non-seed tissue) and mechanical (i.e., harvestability) mechanisms is variable, soybean growers need viable management strategies to mitigate losses caused by this annual pest. As such, there is a need to update current management recommendations for controlling D. texanus; however, several knowledge gaps about D. texanus behavior in the field exist and need to be addressed prior to successful implementation of new management strategies. The major goal of this research was to examine and improve our understanding of the biology and behavior of D. texanus as well as soybean plant responses to infestation through multiple on-farm field experiments. To achieve this, we conducted three field studies. The objectives of the first study were to: 1) monitor adult D. texanus activity within soybean fields to determine if D. texanus adults and/or larvae are aggregated within the field, and if so, 2) identify when during the growing season aggregation occurs. The objective of the second study was to estimate within field dispersal capabilities of adult D. texanus using a protein-based, mark-capture techniques. The final objective was to investigate the utility of vegetation indices as a method to detect soybean infested with D. texanus. To determine if D. texanus adults and or larvae aggregate and when during the growing season we conducted grid sampling throughout June-September, to monitor activity within the field. The results of this study indicate that adult aggregation occurs during July when adult presence is at its highest (mid-late July). By using protein markers, we were able to determine dispersal capabilities of adult D. texanus, within a given soybean field. Results showed that on average D. texanus traveled between 52 to 389 m. Results also found that infested soybean plants had more node and 1% larger stem diameters than non-infested plants. Multiple vegetation indices were used to examine difference in spectral response to D. texanus infestation. Interestingly, only the 2014 exclusion cage study showed a significant difference between D. texanus infested and non-infested cages for several indices, including ENDVI, ENDVI2, ENDVI3, GBNDVI, NIR Green Diff. and NIRBRVI. Given that we were able to detect changes in crop phenology through time, there is great potential in using remote sensing methods to determine optimal times to harvest soybean before D. texanus infestations lodge plants. Such an application would require further investigation.
Keywords: Spatial distribution; Dectes texanus; Cerambycidae; Dispersal; Vegetation index; Protein marking